Sistem Pakar Mendiagnosa Penyakit Sistem Kardiovaskuler Pada Lansia Dengan Menggunakan Metode Case Based Reasoning - Sidabutar, Remita Meliana (JURIKOM (Jurnal Riset Komputer), 2019)
Habits of unhealthy eating patterns can have an adverse effect on health, and can be at risk of disease, in this case cardiovascular system disease. Laypeople often mistakenly think of common symptoms that are felt as symptoms of heart disease and often guess without having knowledge clear about the disease of the cardiovascular system. Expert systems are currently highly developed, where expert systems can provide knowledge designed to model the ability to solve problems like an expert. An expert system was developed in order to be able to assist the tasks of experts with the help of a system that has knowledge, without having to have an expert working in that place. One method used in expert systems is the case based reasoning method. The case based reasoning method is one method that focuses on solving problems in knowledge from previous cases. But in knowing the value of certainty based on the similarity of symptoms with the previous case, the certainty factor method was used.